Response to Intervention for English Learners: Examining Models for Determining Response and Nonresponse. (June 2013) - Richards-Tutor, Catherine; Solari, Emily J.; Leafstedt, Jill M.; Gerber, Michael M.; Filippini, Alexis; Aceves, Terese C.
Using extant data, the purpose of this study is to examine methods for determining response to intervention (RTI) in a sample of kindergarten English Learners (ELs). Three commonly used methods for determining RTI—(a) benchmark criteria, (b) slope discrepancy, and (c) dual discrepancy—are investigated. Participants included 117 ELs. Students were administered pretests and then provided intervention in phonological awareness and phonics in small groups. Progress was monitored weekly on two Dynamic Indicators of Basic Early Literacy Skills measures, Phoneme Segmentation Fluency and Nonsense Word Fluency. Results indicate that there is very little overlap across the three methods and across the two measures in determining response and nonresponse for kindergarten ELs. The results of the study have implications for continued research regarding response of ELs as well as practical implications regarding which methods and measures should be used to determine response.